The Influence of Accounting Information Systems, Quality of Financial Reports, and Effectiveness of Decision Making on Financial Performance at Bali Regional Government Banks - Luh Kardini, Ni; Putu Alit Raga Suryanata, I (Journal of Management, 2025)
This study aims to analyze the influence of Accounting Information Systems (AIS), financial report quality, and decision-making effectiveness on financial performance at the OJK in 2020-2023 at the Bali Regional Development Bank (BPD). Using path analysis, this study found that the AIS has a positive and significant effect on financial performance (β = 0.812, sign = 0.001), where an increase in AIS can improve financial performance by 81.2%. In addition, the quality of financial reports also has a positive and significant effect on financial performance (β = 0.604, sign = 0.000), with an increase in the quality of financial reports potentially increasing financial performance by 60.4%. This study also shows that the AIS has a positive effect on decision-making effectiveness (β = 0.681, sign = 0.001), which then significantly improves financial performance (β = 0.871, sign = 0.000). The quality of financial reports also has a positive effect on the effectiveness of decision-making (β = 0.324, sign = 0.001), which significantly improves financial performance. The analysis results show a strong relationship between AIS, the quality of financial reports, and the effectiveness of decision-making on financial performance, with an R value of 0.842 and an Adjusted R-Square of 0.709. The F-test confirms that all three variables together have a significant effect on financial performance (sign = 0.000). The effectiveness of decision-making plays a significant mediating role in the relationship between AIS and the quality of financial reports on financial performance. This study concludes that improving AIS, the quality of financial reports, and the effectiveness of decision-making are very important for improving the financial performance of Bank BPD Bali.